FAKTOR RISIKO DAN PERILAKU PENCEGAHAN PENYAKIT JANTUNG KORONER PADA LANSIA - Fiona Chalia Putri Ardiany; Ica Natasya Desta Abbelia Pranyoto; Indah Rizky Agus Putri; Irtasari; Izzatur Rosyida Fajrin; Eni Nurhayati (CV. Adiba Aisha Amira, 2025)
Coronary Heart Disease (CHD) is one of the most common cardiovascular diseases and a leading cause of morbidity and mortality, particularly among the elderly in Indonesia. Its prevalence continues to increase with age and physiological changes that make the elderly more vulnerable. The main risk factors for CHD include hypertension, hyperlipidemia, diabetes, obesity, smoking, and decreased physical activity. CHD prevention is crucial through healthy lifestyle modifications, including smoking cessation, maintaining a healthy diet, regular exercise, and regular health check-ups. These efforts are not solely individual, but also require collective support through ongoing education, family involvement, and collaboration between the community, health institutions, and the government. A literature review shows that consistent education and strengthening social support can improve adherence in elderly people to preventive behaviors. Therefore, multifaceted interventions are needed to reduce the incidence of CHD and improve the quality of life of the elderly.